Integrating Mathematical Patterns in Muslim Fashion Design: a 4D-Based Edupreneurship Innovation - Arghob Khofya Haqiqi; Naili Luma’ati Noor; Wakhid Fitri Albar; Hidayah Mohd Fadzil (Hipotenusa: Journal of Mathematical Society, 2025)
The purpose of this study is to develop an innovation "Mathematical Patterns in Muslim Fashion" an innovation in Muslim clothing design using mathematical patterns and to test its feasibility, practicality, and effectiveness for the development of student edupreneurs. The method used in this study is research and development with 4D model, namely define, design, develop, and disseminate. The subjects of this study were students of Mathematics Education at IAIN Kudus who took the Entrepreneurship course in the even semester of the 2022/2023 academic year. The data collection technique in this study used a questionnaire that included feasibility, namely from expert validation, practicality, namely from student responses, and the effectiveness of using Muslim clothing design innovations using mathematical patterns as student edupreneur development. The results of this study are "Mathematical Patterns in Muslim Fashion" Muslim clothing design innovation using mathematical patterns is feasible with material experts with very good criteria, designer validators with good criteria, and edupreneur expert validators with very good criteria, practicality obtained 96%, and effective with very good criteria used as student edupreneur development.